2013
DOI: 10.1073/pnas.1213228110
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of a decellularized skeletal muscle scaffold in a discordant xenotransplantation model

Abstract: Decellularized (acellular) scaffolds, composed of natural extracellular matrix, form the basis of an emerging generation of tissueengineered organ and tissue replacements capable of transforming healthcare. Prime requirements for allogeneic, or xenogeneic, decellularized scaffolds are biocompatibility and absence of rejection. The humoral immune response to decellularized scaffolds has been well documented, but there is a lack of data on the cellmediated immune response toward them in vitro and in vivo. Skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 60 publications
5
137
3
1
Order By: Relevance
“…Furthermore, the authors even suggested that the decellularized scaffold exerts anti-inflammatory and immunosuppressive effects. 35 This may explain why the D-ovary group showed no increase in infiltration with M1 macrophages and CD3…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the authors even suggested that the decellularized scaffold exerts anti-inflammatory and immunosuppressive effects. 35 This may explain why the D-ovary group showed no increase in infiltration with M1 macrophages and CD3…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, ECM materials derived via decellularization of a variety of allogeneic or xenogeneic source tissues have been shown to induce a phenotypic transition from the proinflammatory macrophage and lymphocyte phenotype toward a regulatory, "anti-inflammatory" and healing phenotype [9,31,32,33], and to promote endogenous stem/progenitor cell activation and recruitment [11,29,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…They showed that well-decellularized scaffolds are poorly, if not at all, immunogenic and possibly tolerogenic, while non-well-decellularized tissues are prone to inflammatory response and degradation or encapsulation [24-27]. …”
Section: Discussionmentioning
confidence: 99%